2016
DOI: 10.1155/2016/1764670
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Feasibility of Hydrogen-Rich Gas Production Supported by Iron Based Chemical Looping Process

Abstract: The continuously increasing oil prices as well as stronger environmental regulations regarding greenhouse emissions made the greatest economic powers search a new, price competitive, and environment friendly energy carrier, such as hydrogen. The world research activities in these terms focus on the development of integrated hydrogen and power generating technologies, particularly technologies of hydrogen production from various carbonaceous resources, like methane, coal, biomass, or waste, often combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The above indicates that to exclusively reduce Fe and Cr in the system, there must be a partial pressure of H 2 O less than or equal to 0.0001 atm; when this partial pressure is between 0.0001 and 0.3162 atm, the Fe and Cr 2 O 3 species will predominate and if the partial pressure it is even greater, species such as Fe 3 O 4 , Fe 2 O 3 , Fe(OH) 3 , Cr(OH) 2 will also predominate. Słowi ński and Smoli ński (2016) showed that the introduction of Fe to an H 2 O-rich atmosphere will result in its oxidation to Fe 0.947 O (shown as FeO here) [70]. It can be seen from Figure 2 that Fe is stable in a relatively wide range of H 2 /H 2 O partial pressure ratios at 1000 • C, with decreasing stability as the partial pressure of H 2 O increases.…”
Section: Thermodynamic Considerationsmentioning
confidence: 94%
See 1 more Smart Citation
“…The above indicates that to exclusively reduce Fe and Cr in the system, there must be a partial pressure of H 2 O less than or equal to 0.0001 atm; when this partial pressure is between 0.0001 and 0.3162 atm, the Fe and Cr 2 O 3 species will predominate and if the partial pressure it is even greater, species such as Fe 3 O 4 , Fe 2 O 3 , Fe(OH) 3 , Cr(OH) 2 will also predominate. Słowi ński and Smoli ński (2016) showed that the introduction of Fe to an H 2 O-rich atmosphere will result in its oxidation to Fe 0.947 O (shown as FeO here) [70]. It can be seen from Figure 2 that Fe is stable in a relatively wide range of H 2 /H 2 O partial pressure ratios at 1000 • C, with decreasing stability as the partial pressure of H 2 O increases.…”
Section: Thermodynamic Considerationsmentioning
confidence: 94%
“…The reduction reactions of Fe-and Cr-oxides by hydrogen, in terms of oxidation state changes, will likely follow similar routes as Reactions ( 8)- (13). The equilibrium lines in green color correspond to reduction reactions and considers H 2 O as a by-product: The presence of in-situ formed H 2 O affects Reactions ( 14)- (18), and it has to be taken into account that these reactions proceed as a function of the partial pressure of both H 2 and H 2 O [70,71].…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%
“…For Fe, the reaction equation in each reactor is expressed in eqs –. Many types of materials have been theoretically and experimentally investigated using both natural and artificial particles. In particular, Fe 2 O 3 has attracted much interest because of its potential for storing H 2 energy, owing to its high reactivity for both H 2 storage and production reactions as well as its low cost and low toxicity. …”
Section: Introductionmentioning
confidence: 99%
“…These procedures are either thermochemical (pyrolysis, gasification) [20] or biochemical (anaerobic digestion, fermentation) [21]. Currently, the gasification process uses air, steam [4,22], air-steam [6,19,23], air-oxygen [24], steam-reforming [25] and supercritical water medium [2,12,25]. In [26], a state-of-the-art regarding biomass gasification technologies is presented.…”
Section: Introductionmentioning
confidence: 99%
“…In some thermochemical processes, hydrogen is produced in iron (hematite) and steam based chemical looping process [33,34]. In [22], the iron oxide is firstly reduced with carbon oxide and/or hydrogen (or mixture of both), being subsequently reformed in a reverse reaction with steam, which finally results in pure hydrogen production. In addition, a number of patents address the issue of generating hydrogen from biomass and iron oxides.…”
Section: Introductionmentioning
confidence: 99%